2017
DOI: 10.1104/pp.17.00608
|View full text |Cite
|
Sign up to set email alerts
|

Improving Plant Nitrogen Use Efficiency through Alteration of Amino Acid Transport Processes

Abstract: Improving the efficiency of nitrogen (N) uptake and utilization in plants could potentially increase crop yields while reducing N fertilization and, subsequently, environmental pollution. Within most plants, N is transported primarily as amino acids. In this study, pea (Pisum sativum) plants overexpressing AMINO ACID PERMEASE1 (AAP1) were used to determine if and how genetic manipulation of amino acid transport from source to sink affects plant N use efficiency. The modified plants were grown under low, modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 114 publications
(222 reference statements)
3
103
0
Order By: Relevance
“…As a general concept, N source to sink partitioning is influenced by N uptake and metabolism in source organs, as well as the ability of sources to export, and sinks to import, the N. Studies in Arabidopsis and legumes have demonstrated that amino acid transport processes in the shoot exert regulatory control over N uptake in roots, source metabolism, and allocation to sinks. For example, in pea, increased amino acid phloem loading positively affected N root uptake and, subsequently, N availability for assimilation and usage in source and sink Zhang et al, 2015;Perchlik & Tegeder, 2017). Enhanced N export from leaves and associated changes in leaf N concentrations probably induced a shoot-to-root signal triggering up-regulation of N uptake and delivery to leaves.…”
Section: Relationship Between Source and Sink Nitrogen Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…As a general concept, N source to sink partitioning is influenced by N uptake and metabolism in source organs, as well as the ability of sources to export, and sinks to import, the N. Studies in Arabidopsis and legumes have demonstrated that amino acid transport processes in the shoot exert regulatory control over N uptake in roots, source metabolism, and allocation to sinks. For example, in pea, increased amino acid phloem loading positively affected N root uptake and, subsequently, N availability for assimilation and usage in source and sink Zhang et al, 2015;Perchlik & Tegeder, 2017). Enhanced N export from leaves and associated changes in leaf N concentrations probably induced a shoot-to-root signal triggering up-regulation of N uptake and delivery to leaves.…”
Section: Relationship Between Source and Sink Nitrogen Transportmentioning
confidence: 99%
“…Current knowledge regarding how amino acid transporters are controlled is mostly limited to transcriptional studies. Transporter expression was found to be cell-and tissue-specific, developmentally regulated, and affected by abiotic or biotic factors such as N, light, salt and drought stress, and nematode or pathogen attack (Pratelli & Pilot, 2014;Hav e et al, 2016;Perchlik & Tegeder, 2017). Changes in the redox status or other endogenous factors may induce the transcriptional changes (Geigenberger & Fernie, 2014;Noctor et al, 2015;Bellegarde et al, 2017;Gulyas et al, 2017).…”
Section: Regulation At Cellular Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased NUE of N under warmed plots with unchanged N content indicated that P. maximum acclimates to moderate heating. This response may be associated with changes in N uptake and assimilation, allocation and remobilisation or metabolic modifications [28]. Increased NUE of N may also be achieved by higher transpiration rates.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the rising global demand for food, the NUE must be improved and the application of N fertilizer must be reduced (Hirel, Le Gouis, Ney, & Gallais, 2007; White & Brown, 2010). The main strategy to achieve this is to increase crop yields and reduce N fertilizer application by increasing the UPE and UTE in plants, to ultimately improve NUE and reduce environmental pollution (Perchlik & Tegeder, 2017). Ultimately, this involves achieving an ideal state whereby the maximum N absorption and photosynthetic production can be achieved by optimizing the light, water, and photosynthetic canopy under conditions of the lowest possible N fertilizer application (Fageria, Baligar, & Li, 2008), however, it is difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%